Injuries in French and Chinese regular badminton players - Herbaut, A.; Delannoy, J.; Foissac, M. (Science & Sports, 2018)
Objective: Epidemiological studies examined injuries in European and Asian badminton players but no study directly compared these 2 populations. Therefore, the objective of this study was to examine whether differences existed between French and Chinese regular badminton players (RBP) in terms of injury.